Implementasi Penanggulangan Tuberkulosis di Puskesmas Glugur Darat Kota Medan - Muchti Yuda Pratama; Fitriani Pramita Gurning; Suharto Suharto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to determine the implementation of tuberculosis control policies at Puskesmas Glugur Darat. This research design uses quantitative and qualitative approaches, where the method is a qualitative approach. The results showed that the implementation of the tuberculosis control policy at the Glugur Darat Community Health Center had not run as well as possible. The cure rate for tuberculosis patients at Puskesmas Glugur Darat was 46.15% and less than the national target of> 85% and the treatment success rate of 65.38% was also less than the national target of 85%. In conclusion, the head of the puskesmas, tuberculosis officers, and cadres have used the national tuberculosis guidelines and the DOTS strategy well, but implementation has not gone well because there are still people who do not participate in health promotion activities. Keywords: Land Glug, Implementation, Countermeasures for Tuberculosis Policy